2020
DOI: 10.21203/rs.3.rs-126134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for Use of Damage Control Surgery and Damage Control Interventions in Civilian Trauma Patients: A Systematic Review

Abstract: Background: Although damage control (DC) surgery is widely assumed to reduce mortality in critically injured patients, survivors often suffer substantial morbidity, suggesting that it should only be used when indicated. The purpose of this systematic review was to determine which indications for DC have evidence that they are reliable and/or valid (and therefore in which clinical situations evidence supports use of DC or that DC improves outcomes).Methods: We searched 11 databases (1950-April 1, 2019) for stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Another systematic review conducted by our group in 2018 identified two cohort studies [22,23] that evaluated outcomes associated with implementation or utilization of indications for DC surgery [24]. Rice et al reported that, when compared with minor deviations, moderate or major deviations from a protocol that suggested using DC surgery for patients with a temperature <35°C, lactate >4 mmol/L (or greater than twice the upper limit of normal), or corrected pH <7.3 were independently associated with a significantly reduced survival at 90 days [22,24].…”
Section: Comparative Effectiveness and Safety Of Trauma DC Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…Another systematic review conducted by our group in 2018 identified two cohort studies [22,23] that evaluated outcomes associated with implementation or utilization of indications for DC surgery [24]. Rice et al reported that, when compared with minor deviations, moderate or major deviations from a protocol that suggested using DC surgery for patients with a temperature <35°C, lactate >4 mmol/L (or greater than twice the upper limit of normal), or corrected pH <7.3 were independently associated with a significantly reduced survival at 90 days [22,24].…”
Section: Comparative Effectiveness and Safety Of Trauma DC Surgerymentioning
confidence: 99%
“…Another systematic review conducted by our group in 2018 identified two cohort studies [22,23] that evaluated outcomes associated with implementation or utilization of indications for DC surgery [24]. Rice et al reported that, when compared with minor deviations, moderate or major deviations from a protocol that suggested using DC surgery for patients with a temperature <35°C, lactate >4 mmol/L (or greater than twice the upper limit of normal), or corrected pH <7.3 were independently associated with a significantly reduced survival at 90 days [22,24]. Asensio et al developed a guideline that suggested use of DC surgery in patients who received more than 4 L of packed red blood cells (PRBCs), more than 5 L of PRBCs and whole blood combined, or a total operating room fluid (PRBCs and whole blood, other blood products, and crystalloid) volume replacement of more than 12 L; had a temperature <34°C, serum [HCO3-] ≤15 mEq/L, or arterial pH ≤7.2 during operation; were found to have a thoracic or abdominal vascular injury or complex hepatic injury requiring packing; required emergency department or operating room thoracotomy; or developed intraoperative coagulopathy or dysrhythmias [23,24].…”
Section: Comparative Effectiveness and Safety Of Trauma DC Surgerymentioning
confidence: 99%
See 3 more Smart Citations